Therapeutic applications of eculizumab - Campos-González, Natalia; Ruiz-Jiménez, Susana; Rodríguez-Jiménez, Johanna; Chacón-Jiménez, Luz (Universidad y Salud, 2022)
Introduction: Eculizumab is an IgG type monoclonal antibody designed to treat paroxysmal nocturnal hemoglobinuria (PNH) and its pharmacological target is a member of the complement system. Its mechanism of action has permitted its use in the treatment of orphan diseases such as atypical hemolytic uremic syndrome (aHUS), neuromyelitis optic spectrum disorder (NMOSD), and myasthenia gravis, all of which have a low incidence. Likewise, eculizumab is a viable treatment for Guillain Barré and catastrophic antiphospholipid syndrome (CAS). Objective: To describe the therapeutic applications of eculizumab and its most significant benefits in some illnesses. Materials and methods: A bibliographic search was carried out during the 2010-2021 period in Google Scholar, Science Direct, PubMed y Scielo databases using the keyword eculizumab. Then, the search was refined by using keywords associated with diseases treated with this medication. Results: The mechanism of action of the antibody and its effect on the pathogenesis of paroxysmal nocturnal hemoglobinuria, atypical hemolytic uremic syndrome, refractory generalized myasthenia gravis, neuromyelitis optic spectrum disorder, catastrophic antiphospholipid syndrome, and Guillain Barré were identified. Conclusions: Eculizumab has high safety and capacity in treating and diminishing symptoms of diverse illnesses, which involve the complement system.